Frank confessions: performance in the life-writings of Frank McCourt - Eaton, Margaret Mary Catherine (2016)
This thesis focuses on the work of Frank McCourt, a writer who came to prominence in the 1990s for writing best-selling memoirs that touched upon a wider set of issues in the contemporary cultural debate: namely Ireland itself, the status of the memoir genre, and Irish-American identity. In five distinct chapters, the thesis adopts a postcolonial perspective using the theories of political performance that have been created by Victor Merriman and Joe Cleary to analyse the impact that McCourt’s life-writing and other performances have had upon global impressions of Ireland in the era of the ‘Celtic Tiger’. My thesis combines Merriman’s premise that in performance we can see the basic idea of Irish culture being resistant to modernism and, therefore, Ireland never properly decolonised with Cleary’s notion of disassociation of past and present and his concern with the social and cultural implications of Ireland’s uncritical embrace of a form of capitalist modernisation. Cleary and Merriman’s key ideas are reshaped to uncover the ways in which McCourt creates a version of ‘Irishness’ that is replete with recurrent clichés and stereotypical characters. I make the case that the performative model that McCourt adopts exposes his purpose of creating a national and cultural identity of 1930s and 1940s Ireland in which he reworks and revitalises his impoverished, traumatic childhood, revealing that the identity he expresses is a conscious performance. My analysis reveals how McCourt is engaged in a mode of life-writing that follows his journey from boyhood to manhood in a manner that mirrors the parallel process of Ireland’s journey into independence and economic prosperity when Ireland and ‘Irishness’ became desirable commodities. Throughout, I argue that McCourt utilises performance to market Irish identity successfully to a mass readership since his writing reinforces the connection between his life experience and the narrative of the nation. In turn, the thesis uncovers how McCourt appeals to his Irish and American audiences simultaneously by making use of the dual nationality and fluid identity that being Irish-American affords him, whereby he condemns conditions in Éamon de Valera’s Ireland at the same time that he exhibits a sense of nostalgia for the past. In McCourt’s writing we can recognise many tropes appropriated from films, songs, other memoirs and melodramatic themes, thus providing a meta-textual ‘framework’ by which McCourt’s experiences are organised and given meaning for an audience to understand. As a consequence, each chapter verifies that his deployment of cultural memory and performances of identity function, when ‘read’, to either deconstruct or cement essentialist notions of nationality or ethnicity.